The effects of one versus two episodically oriented practice narratives on children’s reports of a repeated event - Danby, Meaghan C. (Legal and criminological psychology, 2017)
Purpose. Previous research has found that children's reports of repeated events can be influenced by the presence and type of narrative practice in which they engage immediately prior to substantive recall. In particular, children's reports have been shown to benefit from practice providing narratives about an autobiographical repeated event. A gap remains, however, with regard to understanding whether practice narrating one episode of a repeated event encourages children to think about unique features of specific episodes, or whether practice of two episodes is required. The current study addressed this gap. Methods. Five- to nine-year-olds (N = 167) experienced four classroom activity sessions and were later interviewed. Children provided a practice narrative about either one or two episodes of an autobiographical repeated event prior to discussing individual episodes of the activities. Results. Older children recalled more details from the activities when they had practised recalling two episodes compared to one episode. Younger children did not benefit from the second episodic practice. Many similarities were observed across conditions for children of all ages. Conclusions. Older children were likely receptive to the subtle differences between conditions because of their advanced cognitive abilities. Interviewers may assist older children to recall a larger amount of information if they first provide practice recalling two episodes of an autobiographical repeated event. However, a practice narrative about one episode may be sufficient to assist many children should two-episode practice be unfeasible or interviewees are too young to benefit from recall of a second episode.